Pengembangan LKPD Berbasis Open-Ended untuk Meningkatkan Kemampuan Berpikir Kritis Matematis Siswa SMP - Wikari Hulu; Yakin Niat Telaumbanua; Yulisman Zega; Ratna Natalia Mendrofa (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
One effective alternative for students to enhance their understanding of the concepts they are learning through systematic study activities is the use of Student Worksheets (LKPD). There are many mathematical skills that students need to develop, one of which is critical thinking. The ability to think critically in mathematics should be improved. This research employs the Research and Development (R&D) method. The R&D method is used to create a product and evaluate its effectiveness. In this study, the resulting product is the development of open-ended LKPD for the topic of Congruence and Similarity of Plane Figures for eighth-grade students. Based on the results from each validation test, the improvement from the first and second revisions by the material expert validator (Validator 1) showed a percentage increase of 18.59%, and the improvement in assessment by the Validator 1 was 12.1%. The language expert validator showed an improvement of 27.38% from the first to the second revision. The design expert validator showed an improvement of 33.47% from the first to the second revision. Furthermore, the practicality test results indicated that 89.87% of the open-ended LKPD is practical for use in mathematics instruction. Data from the learning achievement test revealed a student mastery percentage of 87%. This indicates that the development of open-ended LKPD for mathematics instruction on the topic of Congruence and Similarity of Plane Figures has a very high level of effectiveness.